A sense of shock the impact of Impressionism on modern British and Irish writing - Parkes, Adam, 1966- (New York ; Oxford : Oxford University Press, 2011)
Examines the various, complex relations between impressionist texts and contexts in modern British and Irish works by Bowen Conrad, Ford, James, Wilde, Woolf, and others, to argue that literary impressionism was an emphatically historical phenomenon.
Description based on print version record.
Includes bibliographical references and index.
Keywords: English literature -- 19th century -- History and criticism; English literature -- 20th century -- History and criticism; Art and literature -- Great Britain -- History -- 19th century; Art and literature -- Great Britain -- History -- 20th century; Impressionism in literature; Visualization in literature; Imagery (Psychology) in literature; Impressionism; Modernism (Literature) -- Great Britain; Literature